PENERAPAN DISIPLIN POSITIF DALAM PEMBELAJARAN JARAK JAUH DI SMP NEGERI 1 BANYUMAS - Mistina Hidayati; Abdul Wachid Bambang Suharto (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2021)
The issue with distance learning in social studies subjects at SMP Negeri 1 Banyumas is students' lack of discipline in responding to and completing assignments assigned by the teacher. According to observations made during the first three months of the odd semester of 2020/2021, the average student attendance rate in distance learning is 75%. Meanwhile, students have an average of 70% discipline when it comes to collecting assignments or responding to the teacher. It is possible because the teacher has not instilled positive discipline in the students, resulting in subpar results. The goal of this research is to describe an overview of positive discipline implementation in the classroom, including the preparation of class agreements, implementation, and results. The findings revealed that implementing positive discipline through class agreement had a positive impact on both teachers and students. The student discipline level in the assignment is 86%, and the average attendance is 90%; the qualifications are excellent. The results of interviews with students conducted via Google Forms and distributed by the teacher regarding the use of positive discipline received a very positive response, with 96.73 percent responding positively. As a result, teachers should use positive discipline during distance learning. This clearly demonstrates that, even when learning is done at a distance, critical assessment of learning can still be conducted.